2015
DOI: 10.1042/bj20150169
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinants of human proton-coupled folate transporter oligomerization: role of GXXXG motifs and identification of oligomeric interfaces at transmembrane domains 3 and 6

Abstract: The human proton-coupled folate transporter (hPCFT) is expressed in solid tumours and is active at pHs characterizing the tumour microenvironment. Recent attention focused on exploiting hPCFT for targeting solid tumours with novel cytotoxic anti-folates. hPCFT has 12 transmembrane domains (TMDs) and forms homo-oligomers with functional significance. The hPCFT primary sequence includes GXXXG motifs in TMD2 (G93XXXG97) and TMD4 (G155XXXG159). To investigate roles of these motifs in hPCFT function, stability and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…Interestingly, the increased surface expression for pt hPCFT and tp hPCFT when MG132 was added to inhibit proteasomal degradation resulted in decreased rather than increased transport activity, probably due to an excess of misfolded protein at the membrane surface. These results are consistent with the notion of a ‘dominant-negative’ interaction between correctly folded and misfolded hPCFT proteins in the context of hPCFT oligomerization [20,21]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, the increased surface expression for pt hPCFT and tp hPCFT when MG132 was added to inhibit proteasomal degradation resulted in decreased rather than increased transport activity, probably due to an excess of misfolded protein at the membrane surface. These results are consistent with the notion of a ‘dominant-negative’ interaction between correctly folded and misfolded hPCFT proteins in the context of hPCFT oligomerization [20,21]. …”
Section: Discussionsupporting
confidence: 91%
“…Human PCFT (hPCFT) is an oligomeric protein [20,21], with each monomer comprising 459 amino acids including 12 transmembrane domains (TMDs), including cytosolic N- and C-termini and a large loop domain connecting TMDs 6 and 7 (Figure 1A). Several studies have used MFS homology considerations and loss-of-function mutations in hPCFT in patients with hereditary folate malabsorption syndrome as a guide for interrogating particular residues in hPCFT that may be structurally or functionally important [2229].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, it has been predicted by topological analyses that Gly 158 constitutes, together with neighbouring Gly 159 , a break point, which is among four of them present in hPCFT TMDs and presumed to play an important role in the conformational change 2,14 . The Gly 158 could also play a role in the functionality of hPCFT through its involvement in the formation of hPCFT oligomers, since G 155 XXXG 159 motif, in which Gly 158 is located, has been suggested to be involved in, together with G 93 XXXG 97 motif in TMD2, intramolecular packing and stability of transmembrane α helices and, thereby, assists homo-oligomerization of hPCFT at the interfaces formed by TMDs 3 and 6 1113 . In addition, the importance of TMD4 in maintaining the integrity and/or functionality of hPCFT has been indicated by the instances of hPCFT defects due to the mutations of G147R and D156Y in TMD4, which were identified in patients of hereditary folate malabsorption 7,8 .…”
Section: Discussionmentioning
confidence: 99%
“…In the loop, Asp 109 , Gly 112 , and Arg 113 have been identified to be of particular importance 610 . For many of the TMDs, their roles in the structure and/or function of hPCFT have been identified, which include TMDs 3 and 6 that play the major role in its homo-oligomerization 1113 , TMDs 2 and 4 that assist the oligomerization by the function of GXXXG motifs (G 93 XXXG 97 in TMD2 and G 155 XXXG 159 in TMD4) 1113 , TMDs 2, 4, and 5 that are involved in substrate binding and translocation 6,12,14 , and TMDs 1, 2, 7, and 11 that forms an extracellular gate 15 . In addition, it has been suggested that TMDs 1, 3, 4, and 6 may potentially form a hydrophobic cavity involved in substrate binding 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of PCFT and RFC are summarized in Figure 2. As with other MFS proteins, PCFT is a homo-oligomer and oligomerization is important to its optimal transport function [77,7,78].…”
Section: Introductionmentioning
confidence: 99%